A novel scoring system to predict cardiac device implantation in patients presenting with syncope. (3rd October 2022) - Khan, A A; Shah, N; Raison, K; Khan, T; Esmail, M; Watkin, R; Basavarajaiah, S
Abstract: Background: Cardiac syncope occurs when the heart fails to maintain cardiac output to match cerebral need and can occur due to either mechanical/structural defect of the heart or secondary to an arrhythmia. It has a raised 1-year mortality with some figures estimating this as high as 30%. Implantable loop recorders (ILR) are a useful diagnostic tool in patients presenting with syncope or pre-syncope to ascertain a cardiac cause. A higher number of patients are presenting with advancing age and undergoing ILR implantation. Subsequently, they end up requiring a cardiac implantable electronic device (CIED) implantation, adding to additional costs, exposure to procedural complications and frequent hospitalisations. Purpose: To investigate the number of patients undergoing CIED implantation following implantation of ILRs for syncope and identify predictors of CIED implantation in patients presenting with syncope. Methods: A retrospective analysis of 736 patients who underwent ILR implantation at our teaching hospital trust between November 2012 to October 2020. Data on demographics, clinical characteristics, pathology results, ECGs, holter findings and CIED implanted was collected using the local electronic patient record system. The data was analysed using SPSS software. Univariable and multivariable regression analysis and ROC curve analysis was carried out to determine prediction model for CIED implantation. Results: The mean age of patients who underwent an ILR implantation was 65±19 years. 22% of patients required CIED implantation, 68% of patients did not require a cardiac device and were safely discharged and 10% of patients died during follow up. Age (p<0.001), male sex (p=0.006), impaired left ventricular function (p=0.04) and presence of hypertension (p=0.04) were found to be independent predictors of CIED implantation on univariable and multivariable regression analysis (see Table 1). Conclusions: Old age, presence of coronary artery disease, impaired left ventricular function and presence of hypertension are inter-linked and in our study were found to be key predictors of poor prognosis and thus requiring CIED implantation. We propose a scoring system based on age >75, male sex, presence of ischaemic heart disease, heart failure and hypertension as key markers of conduction abnormalities requiring CIED implantation (see fi−ure 1). Funding Acknowledgement: Type of funding sources: None.